Analisis Naratif Respons Emosional Orang Tua Pascadiagnosis Anak Berkebutuhan Khusus - Bastiana, Bastiana; Syamsuddin, Syamsuddin; Faizal , Faizal; Sulasminah, Dwiyatmi (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2025)
Parents of children with special needs (CSN) frequently experience intense emotional turmoil following their child's diagnosis. This qualitative study examines the transformation of parents' emotional responses before and after participating in a psychoeducational seminar titled "Educating Children with Special Needs by Understanding Their World." Analysis of twenty spontaneous narratives from parents at SLB Negeri 1 Gowa revealed three predominant pre-seminar themes: feelings of despair and helplessness, uncertainty about the child's future, and profound guilt. Post-seminar, three transformative themes emerged: enhanced acceptance of the child's condition, increased self-confidence in caregiving roles, and the development of social solidarity among participants. These findings highlight the effectiveness of empathetic and participatory psychoeducational interventions in facilitating parental acceptance and building resilience for the long-term support of children with special needs. The study contributes to understanding how structured educational interventions can positively impact parental emotional adaptation to challenging caregiving circumstances.